2016
DOI: 10.1007/s12010-016-2118-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analyses by RNA-seq to Elucidate Differentially Expressed Genes in the Muscle of Korean Thoroughbred Horses

Abstract: The athletic abilities of the horse serve as a valuable model to understand the physiology and molecular mechanisms of adaptive responses to exercise. We analyzed differentially expressed genes in triceps brachii muscle tissues collected from Eonjena Taeyang and Jigusang Seryeok Thoroughbred horses and their co-expression networks in a large-scale RNA-sequence dataset comparing expression before and after exercise. High-quality horse transcriptome data were generated, with over 22 million 90-bp pair-end reads.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In our analysis, HIF1A is not in the top 10, but is also significantly upregulated (FC = 2.33). This is also in agreement with the results of a study in Thoroughbred horses [84]. Furthermore, HIF1A can stimulate promotor elements of PFKFB3 [85], a regulatory molecule that controls glycolysis, which is upregulated (FC = 9.14) in our study but also in other studies [16].…”
Section: Search For Candidate Genes For Endurance Performancesupporting
confidence: 93%
“…In our analysis, HIF1A is not in the top 10, but is also significantly upregulated (FC = 2.33). This is also in agreement with the results of a study in Thoroughbred horses [84]. Furthermore, HIF1A can stimulate promotor elements of PFKFB3 [85], a regulatory molecule that controls glycolysis, which is upregulated (FC = 9.14) in our study but also in other studies [16].…”
Section: Search For Candidate Genes For Endurance Performancesupporting
confidence: 93%
“…Thoroughbred horse is the best breed for racing performance [4]. Thoroughbred horses have been intensively studied as model organisms in the study of exercise, especially at the molecular level, with the Thoroughbred horse genome being well-studied using RNA-seq and the associated epigenetics also receiving significant attention from academics [5,6]. Comparative studies have investigated the differences between Thoroughbred and Jeju horses in order to identify genetic differences using microsatellites [7] and single nucleotide polymorphism (SNP) chip arrays [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The regulator of calcineurin 1 (RCAN1) was reported significantly different in L muscles of Leizhou Black goats in postnatal muscle development [2]. The muscle RNA-seq data from the Eonjena Taeyang horses observed that PPP1R27 shown upregulation at the postexercise period [46]. The protein phosphatase 1 regulatory subunit 27 (PPP1R27) also reported as candidate genes of wool-related traits in Sheep [47].…”
Section: Discussionmentioning
confidence: 99%